Representasi Qudwah Hasanah Dakwah Muslimah Melalui Akun Youtube Hijab Alila - Uky Firmansyah Rahman Hakim (ALAMTARA: Jurnal Komunikasi dan Penyiaran Islam, 2019)
Muslim women perform roles in a video, of course, have limitations and preach through videos on Youtube. Preaching Muslim women must also be an example, not only through strengthening the Qudhwah Hasanah (good example) in the Hijab Alila Youtube Account providing according to the provisions that can be used to promote by packaging video characters using a protector so as not to display Muslim women such as the Dakwah Masa video That and the Good Girl vs. Child Hits, this research uses semiotic analysis of John Fiske to discuss the relationship with three levels, the level of relativity gives a description of the Muslim in relation to and expression in accordance with the rules and courtesy, the level of representation using the camera according to the changes of the players the ideological level of the Hijab Alila content. At the real level the video displays good and bad traits as life after which a message will be given so as not to accept bad behavior. A less praiseworthy character will be played using a mask to maintain the image of a woman The level of camera representation is arranging for medium photography, a long picture to show Muslim women and the level of ideology about beliefs about da'wah that must be fulfilled well.